Studium distribuce prvků v močových kamenech technikou laserové ablace ve spojení s hmotnostní spektrometrií s indukčně vázaným plazmatem - Proksová, Kateřina; Novotný, Karel; Galiová, Michaela; Vaculovič, Tomáš; Kuta, Jan; Nováčková, Monika; Kanický, Viktor (Chemické listy, 2012)
The title technique (LA-ICP-MS) is suitable for mapping of elemental distribution in urinary stones. Two ablation modes have been compared, namely line scan and raster of isolated ablation spots. The correlation between some elements made it possible to estimate the proportions of particular minerals in the urinary stones. The results will be used for comprehensive evaluation of the emergence and growth of urinary stones.
Keywords: Laser Therapy; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Urolithiasis; močové kameny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Chemistry Techniques, Analytical; chemické techniky analytické; laserová terapie; Urinary Calculi; urolitiáza